Klasifikasi Amfibi di Asia Tenggara dengan Penjajaran Sekuen DNA Menggunakan Algoritme Genetika: Classification of Amphibian in Southeast Asia by DNA Sequence Alignment using Genetic Algorithm - Yunita Kristanti Emilia; Agus Wahyu Widodo; Muh. Arif Rahman (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Analysis of DNA sequences is the main thing in the process of classification of amphibians at the family level. One method in sequence analysis is sequence alignment but it requires a large amount of time and cost. The problem of adding gaps and how long gaps are also a problem in the sequence alignment. The amphibian classification process uses genetic algorithms for inserting gaps with several modifications at each stage so that the DNA structure does not change. This study uses two cut point crossover and reciprocal exchange mutation. Fitness scores are used for the classification process by calculating proportions and then convert to evolutionary distance values. The data used were 363 amphibian DNA with 16s rRNA genes divided into five families namely Bufonidae, Dicroglossidae, Megophyridae, Ranidae, Rhacophoridae. Testing the accuracy of the system using the parameters crossover rate = 0.7, mutation rate = 0.3, popsize = 700, number of generations = 900, and multiplier factor = 1.2. System accuracy testing for five families was done 10 times each and got an average accuracy of 94%. With an average accuracy of the system, the genetic algorithm can carry out the sequence alignment process for amphibian classification.